The significance of ethics reflection groups in mental health care: a focus group study among health care professionals - Marit Helene Hem; Bert Molewijk; Elisabeth Gjerberg; Lillian Lillemoen; Reidar Pedersen (BMC Medical Ethics, 2018)
Abstract Background Professionals within the mental health services face many ethical dilemmas and challenging situations regarding the use of coercion. The purpose of this study was to evaluate the significance of participating in systematic ethics reflection groups focusing on ethical challenges related to coercion. Methods In 2013 and 2014, 20 focus group interviews with 127 participants were conducted. The interviews were tape recorded and transcribed verbatim. The analysis is inspired by the concept of ‘bricolage’ which means our approach was inductive. Results Most participants report positive experiences with participating in ethics reflection groups: A systematic and well-structured approach to discuss ethical challenges, increased consciousness of formal and informal coercion, a possibility to challenge problematic concepts, attitudes and practices, improved professional competence and confidence, greater trust within the team, more constructive disagreement and room for internal critique, less judgmental reactions and more reasoned approaches, and identification of potential for improvement and alternative courses of action. On several wards, the participation of psychiatrists and psychologists in the reflection groups was missing. The impact of the perceived lack of safety in reflection groups should not be underestimated. Sometimes the method for ethics reflection was utilised in a rigid way. Direct involvement of patients and family was missing. Conclusion This focus group study indicates the potential of ethics reflection groups to create a moral space in the workplace that promotes critical, reflective and collaborative moral deliberations. Future research, with other designs and methodologies, is needed to further investigate the impact of ethics reflection groups on improving health care practices.